Respon M. M. Azami Terhadap Orientalis Berkaitan Dengan Otentitas Hadis - Amelia, Rizqa; Rahayu, Sri Ulfa (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
Among the several views on Hadith studies that have emerged and are quite controversial are those originating from orientalists who state that the authenticity of hadiths is not as pure as what Muslims have believed so far, on the consideration that none of the Prophet's Hadiths are purely authentic from the Prophet, especially the hadiths of the Prophet hadith with ahad narration. Which then seems to explain that, it is rather difficult to believe the hadith literature as a whole as an authentic record of all the sayings and practices that originate from the Prophet Muhammad saw. Even among Muslims, there are groups that claim to believe in the Al-Qur'an, but are against the hadith of the Prophet. This polemic naturally invites various reactions from Muslim researchers, especially those who are concerned with Hadith studies. One of them is M. M. Azami, a leading hadith researcher. M.M. Azami found that the doubts expressed by orientalists regarding the sanad system were due to their methodological errors in studying the study of sanad material, because in general they did not study the chain of transmission based on the main books of hadith, but based on the main books of hadith, the fiqh and sirah which are arranged in a different way from the books of hadith. M.M. Azami responds to the views of orientalists and proves the authenticity of hadith in several ways, including: explaining the method of writing the Prophet's hadith, the system for transmitting the Prophet's Hadith, the system of using sanad, reasoning criticism, and comparative methods